Mini Review An-overview on Buffalo Condensed Milk and its Products with Emphasis of Their Biochemical Properties: Mini Review: Biochemical Properties of Buffalo Codensed Milk (Biological Sciences - PJSIR, 2021)
In this review an-overview is presented to study the effects of condensation, skimming and physio-chemical quality of buffalo milk. Skimming process had significant influences on chemical and sensory qualities of milk. Previous researchers discussed the remarkable changes in the physical and physio- chemical characteristics of condensed milk i.e. moisture, ash content and acidity, specific gravity of skimmed milk as compared to the whole milk. It has been also concluded from the different studies that the physical properties like, exterior, colour, flavour and body texture of milk were comparatively reduced by condensation and skimming and the density of skimmed milk appeared thinner and products achieved the variable score in different above mentioned physio-chemical properties. This review will discuss the effects of condensation and skimming on whole milk and their byproducts and their physical and physio- chemical properties in comparative aspects skimming and condensation whole milk.